The model of mining environment restoration regulation based on Sustainable Development Goals - Kadir Jaelani, Abdul; Octavia Kusumaningtyas, Reza; Orsantinutsakul, Asron (Legality : Jurnal Ilmiah Hukum, 2022)
This article aimed to discuss mining environment restoration regulations. The government has established a number of policies concerning reclamation and post-mining. However, the critical question is whether these policies can ensure the rehabilitation of the mining environment in accordance with sustainable development goals, given the numerous unreclaimed and abandoned mining pits that have resulted in several fatalities. The purpose of this study is to examine reclamation and post-mining management standards in order to reduce the environmental damage caused by mining activities. This normative legal study gathered data from documents examined qualitatively. The data analysis is descriptive-analytic in nature. The study's findings indicate that environmental law enforcement in the mining sector continues to face significant challenges. There is a need to enhance legislation and systems governing mining management. Standardization of reclamation and post-mining management is necessary to offer rules for implementation that suit the needs of the community. It has no adverse effect on the community surrounding the mining location. Licensing is one policy that can apply to implement standardization. Supervising land management following mining, management of waste, and developing policies promote environmentally friendly mining and conservation activities.